Long‐term forest resilience to climate change indicated by mortality, regeneration, and growth in semiarid southern Siberia. (28th December 2016) - Xu, Chongyang; Liu, Hongyan; Anenkhonov, Oleg A.; Korolyuk, Andrey Yu; Sandanov, Denis V.; Balsanova, Larisa D.; Naidanov, Bulat B.; Wu, Xiuchen
Abstract: Several studies have documented that regional climate warming and the resulting increase in drought stress have triggered increased tree mortality in semiarid forests with unavoidable impacts on regional and global carbon sequestration. Although climate warming is projected to continue into the future, studies examining long‐term resilience of semiarid forests against climate change are limited. In this study, long‐term forest resilience was defined as the capacity of forest recruitment to compensate for losses from mortality. We observed an obvious change in long‐term forest resilience along a local aridity gradient by reconstructing tree growth trend and disturbance history and investigating postdisturbance regeneration in semiarid forests in southern Siberia. In our study, with increased severity of local aridity, forests became vulnerable to drought stress, and regeneration first accelerated and then ceased. Radial growth of trees during 1900–2012 was also relatively stable on the moderately arid site. Furthermore, we found that smaller forest patches always have relatively weaker resilience under the same climatic conditions. Our results imply a relatively higher resilience in arid timberline forest patches than in continuous forests; however, further climate warming and increased drought could possibly cause the disappearance of small forest patches around the arid tree line. This study sheds light on climate change adaptation and provides insight into managing vulnerable semiarid forests. Abstract : In this study, long‐term forest resilience was defined as the capacity of forest recruitment to compensate for losses from mortality, to examine long‐term resilience of semiarid forests against climate change in southern Siberia of Russia. With increased severity of local aridity, forests became vulnerable to drought stress, and regeneration first accelerated and then ceased. Smaller forest patches always have relatively weaker resilience under the same climatic conditions.